Evolution of surface and sub-surface morphology and chemical state of exsolved Ni nanoparticles. (11th May 2022) - Kersell, Heath; Weber, Moritz L.; Falling, Lorenz; Lu, Qiyang; Baeumer, Christoph; Shirato, Nozomi; Rose, Volker; Lenser, Christian; Gunkel, Felix; Nemšák, Slavomír
Abstract : Dynamic surface and subsurface morphology and chemistry of socketed nanoparticles is monitored in situ for an important emerging class of nanoparticles. Abstract : Nanoparticle formation by dopant exsolution (migration) from bulk host lattices is a promising approach to generate highly stable nanoparticles with tunable size, shape, and distribution. We investigated Ni dopant migration from strontium titanate (STO) lattices, forming metallic Ni nanoparticles at STO surfaces. Ex situ scanning probe measurements confirmed the presence of nanoparticles at the H2 treated surface. In situ ambient pressure X-ray photoelectron spectroscopy (AP-XPS) revealed reduction from Ni 2+ to Ni 0 as Ni dopants migrated to the surface during heating treatments in H2 . During Ni migration and reduction, the Sr and Ti chemical states were mostly unchanged, indicating the selective reduction of Ni during treatment. At the same time, we used in situ ambient pressure grazing incidence X-ray scattering (GIXS) to monitor the particle morphology. As Ni migrated to the surface, it nucleated and grew into compressed spheroidal nanoparticles partially embedded in the STO perovskite surface. These findings provide a detailed picture of the evolution of the nanoparticle surface and subsurface chemical state and morphology as the nanoparticles grow beyond the initial nucleation and growth stages.